2003
DOI: 10.1007/s00415-003-1091-3
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizure after stroke in Chinese patients

Abstract: This was a hospital-based cohort study aiming at determining the occurrence rate of post-stroke seizures and the associated risk factors. From 27 July 1996 to 16 June 1998, the first 1000 consecutive patients in the acute stroke registry were retrospectively reviewed for one year after acute stroke to identify seizure occurrence. The demographic data, seizure onset time, seizure type, drug treatment, response to medication, electroencephalogram findings and cranial computed tomogram findings were collected. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 15 publications
4
50
1
5
Order By: Relevance
“…Although the frequency of seizures after spontaneous ICH is estimated at 2.8-18.7%, 1,3,4,6,9,14,15,19 much of these data were based on retrospective studies with variable follow-up. In our study, seizures occurred in 20 (8.2%) of the 243 patients who had spontaneous ICH, including acute symptomatic seizures in 9 patients (3.7%) and unprovoked seizures in 11 (4.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the frequency of seizures after spontaneous ICH is estimated at 2.8-18.7%, 1,3,4,6,9,14,15,19 much of these data were based on retrospective studies with variable follow-up. In our study, seizures occurred in 20 (8.2%) of the 243 patients who had spontaneous ICH, including acute symptomatic seizures in 9 patients (3.7%) and unprovoked seizures in 11 (4.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy in patients who have had spontaneous ICH may have delayed manifestation, but most occur within 2 years. 1 Epileptic seizures after spontaneous ICH have been reported in 2.8-18.7% of patients in various studies, 1,3,4,6,9,14,15,19 and seizures only in patients with strokes and cerebral hemisphere lesions. 4,18 The indications for and duration of seizure treatment required after spontaneous ICH remain controversial, although Passero et al 18 recently demonstrated that the risk of early seizures was reduced with prophylactic AED therapy in patients with lobar ICH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] İnme sonrası nöbet gelişmesi için risk faktörleri olarak bazı çalışmalarda hemorajik inme, kardiyo-embolik inme, inme şiddeti, kortikal yerleşim, birden fazla lobun tutulumu gibi faktörler bildirilmektedir. [7] Bu çalışmada inme sonrası nöbet gelişen olgularda klinik özellikler ve bu özelliklerin prognoz ile ilişkisi değerlendiril-miştir. Anterior sirkülasyon tutulum sıklığı erken ve geç nöbet gruplarında birbirine eşit bulundu (%78).…”
Section: Introductionunclassified
“…In the literature, stroke severity was found to be a predictor of clinical poststroke seizures in some studies, [21][22][23][24] but not all. 25 Recent elec- trophysiologic studies using cEEG in patients admitted to an intensive care unit 7,8 did not find stroke severity to be a predictor of electrical epileptic seizures.…”
mentioning
confidence: 99%